Sasaki Green: A Sustainable Planning Guide. - Jacob, Meenakshi.; Ladd, Audra.; Nicholson, Craig.; McEntee, Jesse.; Wood, Jennifer. (Tufts University. Tisch Library., 2018)
2006 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Sasaki Associates.